Mengukur Determinasi Faktor-Faktor yang Memengaruhi Nilai Aktiva Bersih (NAB) Saham Syariah di Indonesia - Yudhistira Ardana; Salma Khoirunnisa; Kurnia Fadilah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Sharia mutual funds in Indonesia continue to experience significant development. The number of mutual fund products is always increasing every year. There are several factors that influence the development of Islamic mutual funds in Indonesia. In addition to economic conditions, investment managers who manage sharia mutual funds are very important. This is because the investment manager plays an important role in circulating the funds managed by customers. This study aims to measure the factors that affect the Net Asset Value (NAV) of Islamic equity mutual funds in Indonesia by using a panel data model. The variables used are inflation (X1), interest rates (X2), exchange rates (X3), Jakarta Islamic Index (X4), mutual fund volume (X5), and age of mutual funds (X6) and Net Asset Value (NAV) of Islamic stock mutual funds. (Y). The best model used in this research is the random-effect panel data model. The estimation results show that simultaneously, all the variables used in this study have a significant effect on the Net Asset Value (NAV) of Islamic equity mutual funds in Indonesia with a percentage of 92.35%. Partially, inflation and exchange rate variables have a significant negative effect. Meanwhile, interest rates, the Jakarta Islamic Index, mutual fund volume, and the age of mutual funds have a significant positive effect on the NAV of Islamic stock mutual funds.